Central-metal exchange, improved catalytic activity, photoluminescence properties of a new family of d10 coordination polymers based on the 5, 5′-(1H-2, 3, 5-triazole-1, 4-diyl)diisophthalic acid ligand. Issue 18 (11th April 2016) - Wang, Huarui; Huang, Chao; Han, Yanbing; Shao, Zhichao; Hou, Hongwei; Fan, Yaoting
Abstract : Five d 10 coordination polymers (CPs) have been successfully isolated. Central-metal exchange in CP2 leads to a series of isostructural M(ii )–Cd CPs (M = Cu, Co, Ni) showing improved catalytic activity. Abstract : The rigid and planar tetracarboxylic acid 5, 5′-(1 H -2, 3, 5-triazole-1, 4-diyl)diisophthalic acid (H4 L), incorporating a triazole group, has been used with no or different pyridine-based linkers to construct a family of d 10 coordination polymers, namely, {[H2 N(CH3 )2 ]3 [Cd3 (L)2 (HCOO)]} n (1 ), {[Cd2 (L)(py)6 ]·H2 O} n (2 ), {[H2 N(CH3 )2 ] [Cd2 (L)(HCOO)(H2 O)4 ]} n (3 ), {[Zn(H2 L)]·H2 O} n (4 ), and {[Zn(H2 L)(4, 4′-bipy)0.5 ]·C2 H5 OH·H2 O} n (5 ) (py = pyridine, 4, 4′-bipy = 4, 4′-bipyridine).1 constructs a 3D porous network containing two kinds of channels: one is filled with coordinated HCOO − anions, and the other with [H2 N(CH3 )2 ] + cations. The framework of1 can be described as a rare (5, 6, 7)-connected net with the Schläfli symbol of (4 12 ·5·6 2 )(4 5 ·5 3 ·6 2 )2 (4 8 ·5 3 ·6 8 ·8 2 )2 . The Cd(ii ) ions in2 are connected through the carboxylate ligands to form a 2D layer, with aperture dimensions of ∼15.1 Å × 16.2 Å. The network of3 features a 3D (3, 4)-connected (6·8·10)2 (6·8 3 ·10 2 ) topology. A 3D network with the (4 2 ·6·8 3 ) topology of4 possesses an open 1D channel with the free volume of 29.2%.5 is a 2D layer structure with the (4 2 ·6 3 ·8)(4 2 ·6) topology. The fluorescence lifetime τ values of1–5 are on the nanosecond timescale at room temperature. In particular, central-metal exchange in2 leads to a series of isostructural M(ii )–Cd frameworks [M = Cu (2a ), Co (2b ), Ni (2c )] showing improved catalytic activity for the synthesis of 1, 4, 5, 6-tetrahydropyrimidine derivatives. Based on this, a plausible mechanism for the catalytic reaction has been proposed and the reactivity–structure relationship has been further clarified.